Improving Ballistic Performance of Polyurethane Foam by Nanoparticle Reinforcement. (26th January 2010) - Uddin, M. F.; Mahfuz, H.; Zainuddin, S.; Jeelani, S.
Abstract : We report improving ballistic performance of polyurethane foam by reinforcing it with nanoscaleTiO 2 particles. Particles were dispersed through a sonic cavitation process and the loading of particles was 3 wt% of the total polymer. Once foams were reinforced, sandwich panels were made and impacted with fragment simulating projectiles (FSPs) in a 1.5-inch gas gun. Projectile speed was set up to have complete penetration of the target in each experiment. Test results have indicated that sandwich with nanophased cores absorbed about 20% more kinetic energy than their neat counterpart. The corresponding increase in ballistic limit was around 12% over the neat control samples. The penetration phenomenon was also monitored using a high-speed camera. Analyses of digital images showed that FSP remained inside the nanophased sandwich for about 7 microseconds longer than that of a neat sandwich demonstrating improved energy absorption capability of the nanoparticle reinforced core. Failure modes for energy absorption have been investigated through a microscope and high-speed images.